Suicide and Predicament - Pridmore, Saxby (Bentham Science Publishers, 2010)
"Suicide and Predicament: Life is a Predicament" takes a broad view of suicide. It argues that a large proportion of people who suicide do not have a mental disorder, and therefore it is essential to know about the predicaments of people. The book draws on sociology and takes issue with the medicalization of distress and suicide. It discusses genetics and draws attention to the importance of alcohol in suicide. It takes as examples, 127 suicide cases found in public record. Unique features of the ebook include 1) predicament model, 2) pathways model, 3) typology of suicide, and 4) prevention initiatives.